Operative Treatment Options for Patellofemoral Arthritis: An Expert Recommendation of the AGA Patellofemoral Committee. Issue 3 (12th March 2021) - Keshmiri, Armin; ,; Dirisamer, Florian; Liebensteiner, Michael; El Attal, Rene; Pagenstert, Geert; Seitlinger, Gerd; Wagner, Daniel; Balcarek, Peter; Kappel, Paola; Schöttle, Philip; Frings, Jannik; et al.
Background: The operative therapy of patellofemoral arthritis requires an individual approach depending on the underlying injury. However, the literature lacks recommendations for its course of action. Purpose: To generate an expert recommendation of therapy for different patellofemoral abnormalities in patients suffering from isolated patellofemoral arthritis. Study Design: Consensus statement. Methods: To generate recommendations, the AGA Patellofemoral Committee performed a consensus process using the Delphi method based on the available literature on isolated patellofemoral arthritis. Results: In most statements and recommendations, a high percentage of consensus could be found. However, also in the expert group of the AGA Patellofemoral Committee, some controversies on the treatment of patellofemoral arthritis exist. Conclusion: The operative therapy of isolated patellofemoral arthritis is a challenging topic that leads to controversial discussions, even in an expert group. With this consensus statement of the AGA Patellofemoral Committee, recommendations on different operative treatment options were able to be generated, which should be considered in clinical practice.